"Global myocardial ischaemia after PDA ligation" – An anomaly with duct dependant coronary circulation?!. (24th May 2012) - Jamalpuri, V; Tulloh, T; Onuzo, O
Abstract : A 5 month old infant presented to referring hospital with respiratory distress and growth faltering. Growth faltering investigations included an echocardiogram which showed large PDA with left to right shunt, mild to moderate mitral regurgitation, dilated left atrium and left ventricle. She was referred to our cardiac surgical centre for duct ligation. She underwent PDA ligation and developed ventricular fibrillation post operatively. The infant was defibrillated and converted to sinus rhythm. An ECG showed features of global ischaemia. Trans-thoracic echocardiogram revealed an Anomalous Left Coronary Artery from Pulmonary Artery (ALCAPA). The anomalous coronary artery was reimplanted into the aortic root. She made a good recovery post-operatively after three day intensive care. Clinical features of ALCAPA are generally due to myocardial ischaemia secondary to low pressure coronary circulation and poorly oxygenated blood1 . In our patient, the presence of a large PDA prevented fall in pulmonary artery pressure and maintained the antegrade blood flow to the left coronary artery until it was ligated. ALCAPA is a rare cardiac anomaly occurring in one of 300 000 live births1 . It is usually an isolated anomaly, but rarely be associated with other left to right shunts1 – 3 . ALCAPA should be considered when ischaemia follows an acute reduction in pulmonary artery pressure. Previous reports have described fatal outcomes after ligation of a PDA in patients with undiagnosed ALCAPA2, 3 . Our case once again emphasises the importance of demonstrating the coronary artery anatomy in all patients before surgical closure of left to right shunt lesions.